Protection of historic ruins - objectives for theory and practice - Szmygin, Bogusław (Protection of Cultural Heritage, 2018)
The protection of historic ruins is a complex conservation task. This is mainly due to the ongoing destruction processes to which an incomplete object is exposed. At the same time, the character of the ruins means that most of the stakeholders support the reconstruction of historic ruins to the form of cubature objects. Therefore, the problem of protecting the ruins should be re-developed both from the theoretical as well as the practical side. From the theoretical point of view, it is important to distinguish between "historic ruin" and "contemporary ruin". From a practical point of view, it is crucial to organize protection programs that will balance the negative features of the ruins - not only will they stop the technical destruction processes but also will enable their contemporary management and use.